Performance of geographic routing protocol in mobile ad-hoc networks - Uddin, Jia; Haque, Mohammad Ariful; Kim, Jongmyon; Kim, Cheolhong; Yi, Myeongjae; Kim, Taegong (© 2014 International Information Institute Ltd., 2016)
This article was published in the International Journal of Multimedia and Ubiquitous Engineering [© 2014 Information (Japan)]